Odpowiedź :
3 do potęgi 2+b2=6 do potęgi 2
9+b2=36
b2=36-9
b2=27
b=3 pierwiastek z 3
2 do potęgi 2+2 pierwiastek z 2 do potęgi 2=c2
4+2=c2
-c2=-4-2
-c2=6
-c=2 pierwiastek z 2
c=2 pierwiastek z 2
4 do 2+b2=4 pierwiastek z 2 do 2
16+b2=16x2
b2=32-16
b2=16
b=4
2 do 2+b2=2 pierwiastek z 3 do 2
4+b2=4x3
b2=12-4
b=2 pierwiastek z 2
a2+4 pierwiastek z 3 do 2=8 do 2
a2+16x3=64
a2=64-48
a2=16
a=4
3 do 2+3 do 2=c2
9+9=c2
c2=9-9
c2=0
5 do 2+5 pierwiastek z 3 do 2=c2
25+25x3=c2
25+75=c2
c2=75-25
c2=50
c=5 pierwiastek z 2
9+b2=36
b2=36-9
b2=27
b=3 pierwiastek z 3
2 do potęgi 2+2 pierwiastek z 2 do potęgi 2=c2
4+2=c2
-c2=-4-2
-c2=6
-c=2 pierwiastek z 2
c=2 pierwiastek z 2
4 do 2+b2=4 pierwiastek z 2 do 2
16+b2=16x2
b2=32-16
b2=16
b=4
2 do 2+b2=2 pierwiastek z 3 do 2
4+b2=4x3
b2=12-4
b=2 pierwiastek z 2
a2+4 pierwiastek z 3 do 2=8 do 2
a2+16x3=64
a2=64-48
a2=16
a=4
3 do 2+3 do 2=c2
9+9=c2
c2=9-9
c2=0
5 do 2+5 pierwiastek z 3 do 2=c2
25+25x3=c2
25+75=c2
c2=75-25
c2=50
c=5 pierwiastek z 2